Association Between Preeclampsia and Congenital Heart Defects. Issue 3 (September 2016) - Auger, N.; Fraser, W.D.; Healy-Profitós, J.; Arbour, L.
Abstract : ( JAMA. 2015;314(15):1588–1598) Congenital heart defects are the most common anomaly in infants and are a major cause of infant morbidity and mortality. The origins of congenital heart defects, therefore, need to be better studied in order to improve prevention and earlier detection. Recent studies have tried to identify biomarkers for congenital heart defects as well as preeclampsia. Biomarker findings associated with heart defects include imbalances in proangiogenic signaling proteins, such as vascular endothelial growth factor and placental growth factor, and antiangiogenic proteins, such as soluble endoglin and fms-like tyrosine kinase 1. Imbalances in these same biomarkers have been found with preeclampsia, where there is an excess of soluble endoglin and fms-like tyrosine kinase 1 relative to placental growth factor and vascular endothelial growth factor. Angiogenic mechanisms may be part of a shared pathologic pathway for preeclampsia and congenital heart defects. Studies have shown that the pathologic changes associated with preeclampsia begin early in pregnancy, around the time that fetal heart development is occurring. This current study tried to determine the relationship between preeclampsia and the prevalence of congenital heart defects in infants whose mothers had the disorder.